Development Of Mathematics Learning Modules On Relations And Functions - Ramadani, Ayutia; Yahfizham; Siregar, Tanti Jumaisyaroh (Mahir : Jurnal Ilmu Pendidikan dan Pembelajaran, 2023)
This study aims to: (1) Know the feasibility of the Mathematics Learning Module used by students in learning mathematics on the subject of Relations and Functions, (2) Know the practicality of the Mathematics Learning Module used by students on learning mathematics on the material of Relations and Functions, (3) Know the effectiveness The Mathematics Learning Module used by students in learning mathematics on the subject of Relations and Functions. The results of the development of this learning module show that the average score obtained shows the criteria of "good" and is feasible to be tested in the field. Then the practicality of developing this module is also in the "good" criteria. As well as the effectiveness of this learning module to obtain an average score with good criteria to be used as teaching materials in the field.